Pop-Up Books as Interactive Learning Media: Effects on Eighth-Grade Students' Reading Comprehension Skills - Rafida Nurul Azizah; Ella Wulandari (Universitas Ahmad Dahlan, 2026)
This study examined the effects of pop-up books as interactive learning media on eighth-grade students' reading comprehension skills. Employing a quasi-experimental nonequivalent comparison-group design, 66 eighth-grade students from a junior high school were divided into experimental (N=33) and control (N=33) groups. The experimental group received instruction using pop-up books, while the control group used conventional worksheets. Data were collected through pre-tests and post-tests, then analyzed using SPSS 22.00 with descriptive and inferential statistics. Results revealed significant differences between groups. The experimental group's mean score increased from 68.03 to 75.76, while the control group decreased from 73.03 to 68.48. Independent t-test results showed t(64)=2.809, p=0.007, indicating significant differences in reading comprehension skills between students taught using pop-up books and those using worksheets. These findings demonstrate that pop-up books effectively enhance students' reading comprehension through their interactive features, visual appeal, and multi-sensory learning experiences, thereby addressing student engagement challenges in narrative text comprehension.